2023
DOI: 10.1002/app.53949
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of terephthalic acid yield in aqueous hydrolysis of polyethylene terephthalate

Abstract: Aqueous hydrolysis is used to chemically recycle polyethylene terephthalate (PET) due to production of high‐quality terephthalic acid (TPA), the PET monomer. PET hydrolysis depends on various factors including PET size, catalyst concentration, and reaction temperature. So, modeling PET hydrolysis by considering the effective factors can provide useful information for material researchers to specify how to design and run these reactions. It will save time, energy, and materials by optimizing the hydrolysis cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…It is challenging to compare the results obtained herein with those reported in the literature for neutral hydrolysis reactions, because of the wide variety of operational conditions reported and PET substrate properties/morphologies. 13,16,56 Pereira et al have reported a TPA yield <10% when PET chips from sparking water bottles were hydrolyzed at 200 °C for 120 min. 13 It is worth mentioning that when we performed hot compressed H 2 O reactions (in the absence of N 2 ) a TPA yield <5% was observed at 200 °C for 100 min (Table S2†), which is in good agreement with the findings reported by Pereira et al who did not use N 2 to pressurize the H 2 O in those experiments.…”
Section: Resultsmentioning
confidence: 99%
“…It is challenging to compare the results obtained herein with those reported in the literature for neutral hydrolysis reactions, because of the wide variety of operational conditions reported and PET substrate properties/morphologies. 13,16,56 Pereira et al have reported a TPA yield <10% when PET chips from sparking water bottles were hydrolyzed at 200 °C for 120 min. 13 It is worth mentioning that when we performed hot compressed H 2 O reactions (in the absence of N 2 ) a TPA yield <5% was observed at 200 °C for 100 min (Table S2†), which is in good agreement with the findings reported by Pereira et al who did not use N 2 to pressurize the H 2 O in those experiments.…”
Section: Resultsmentioning
confidence: 99%